Mammographic compression after breast conserving therapy: Controlling pressure instead of force. Issue 2 (23rd January 2014) - de Groot, J. E.; Broeders, M. J. M.; Branderhorst, W.; den Heeten, G. J.; Grimbergen, C. A.
Abstract : Purpose: : X‐ray mammography is the primary tool for early detection of breast cancer and for follow‐up after breast conserving therapy (BCT). BCT‐treated breasts are smaller, less elastic, and more sensitive to pain. Instead of the current force‐controlled approach of applying the same force to each breast, pressure‐controlled protocols aim to improve standardization in terms of physiology by taking breast contact area and inelasticity into account. The purpose of this study is to estimate the potential for pressure protocols to reduce discomfort and pain, particularly the number of severe pain complaints for BCT‐treated breasts. Methods: : A prospective observational study including 58 women having one BCT‐treated breast and one untreated nonsymptomatic breast, following our hospitalˈs 18 decanewton (daN) compression protocol was performed. Breast thickness, applied force, contact area, mean pressure, breast volume, and inelasticity (mean E‐modulus) were statistically compared between the within‐women breast pairs, and data were used as predictors for severe pain, i.e., scores 7 and higher on an 11‐point Numerical Rating Scale. Curve‐fitting models were used to estimate how pressure‐controlled protocols affect breast thickness, compression force, and pain experience. Results: : BCT‐treated breasts had on average 27% smaller contact areas, 30% lower elasticity, and 30% higher pain scores than untreated breasts (all p < 0.001). Contact area was the strongest predictor for severe pain ( p < 0.01). Since BCT‐treatment is associated with an average 0.36 dm 2 decrease in contact area, as well as increased pain sensitivity, BCT‐breasts had on average 5.3 times higher odds for severe pain than untreated breasts. Model estimations for a pressure‐controlled protocol with a 10 kPa target pressure, which is below normal arterial pressure, suggest an average 26% (range 10%–36%) reduction in pain score, and an average 77% (range 46%–95%) reduction of the odds for severe pain. The estimated increase in thickness is +6.4% for BCT breasts. Conclusions: : After BCT, women have hardly any choice in avoiding an annual follow‐up mammogram. Model estimations show that a 10 kPa pressure‐controlled protocol has the potential to reduce pain and severe pain particularly for these women. The results highly motivate conducting further research in larger subject groups.